OBSERVATION OF COUPLED AMPLITUDE MODES IN THE RAMAN-SPECTRUM OF INCOMMENSURATE GAMMA-NA2CO3 - Maciel, A; Ryan, J (1981)
Temperature-dependent phonons have been observed in the Raman spectrum of incommensurate psi -Na2CO3. Two modes are identified as q approximately=0 librational modes of the CO32- groups, which soften at the alpha - beta transition at Tc1=763K. At T c2=633K a modulation of the structure sets in which is believed to be due to a softening of a librational mode at the incommensurate wavevector q*. Two additional lines that the authors observe in the gamma -phase are assigned to coupled amplitude modes that arise from the coupling of acoustic and librational branches at q=q*.